Firms’ knowledge search and local knowledge externalities in innovation performance - Roper, Stephen; Love, James H.; Bonner, Karen (Research policy, 2017)
•We explore firm-level and local area openness externalities on firms’ innovation performance.•Strong effects of both interactive collaboration and non-interactive contacts such as demonstration effects or copying.•Strong positive externalities of openness resulting from the intensity of local interactive knowledge search.•But also strong negative externalities resulting from the intensity of local non-interactive knowledge search.•Results provide support for local initiatives to support innovation partnering and counter illegal copying. We use an augmented version of the UK Innovation Surveys 4–7 to explore firm-level and local area openness externalities on firms’ innovation performance. We find strong evidence of the value of external knowledge acquisition both through interactive collaboration and non-interactive contacts such as demonstration effects, copying or reverse engineering. Levels of knowledge search activity remain well below the private optimum, however, due perhaps to informational market failures. We also find strong positive externalities of openness resulting from the intensity of local interactive knowledge search—a knowledge diffusion effect. However, there are strong negative externalities resulting from the intensity of local non-interactive knowledge search—a competition effect. Our results provide support for local initiatives to support innovation partnering and counter illegal copying or counterfeiting. We find no significant relationship between either local labour quality or employment composition and innovative outputs.